Polymorphisms in TLR2 are associated with increased viral shedding and lesional rate in patients with genital herpes simplex virus Type 2 infection - Bochud, Pierre-Yves; Magaret, Amalia S; Koelle, David M; Aderem, Alan; Wald, Anna (The Journal of infectious diseases, 2007)
Clinical and virologic manifestations of genital herpes simplex virus type 2 (HSV-2) infection vary widely. We examined frequencies of single-nucleotide polymorphisms (SNPs) in Toll-like receptors (TLRs) 2, 3, 4, and 9 in a prospective cohort of 128 HSV-2-infected persons whose viral shedding and lesion frequency was measured by daily sampling from genital secretions. Two TLR2 haplotypes (2 and 4) were associated with increased lesional (P=.008 and P=.03) and shedding (P=.02 and P=.001) rates. An SNP in haplotype 2 (-15607A/G) was also associated with shedding (P=.01) and lesional (P=.008) rates. Polymorphisms in TLR2 may be in part responsible for differences in the severity of HSV-2 infection.